2019
DOI: 10.1186/s12879-019-3683-2
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analysis of isavuconazole versus voriconazole for the treatment of patients with possible invasive aspergillosis in Sweden

Abstract: BackgroundVoriconazole is well established as standard treatment for invasive aspergillosis (IA). In 2017, isavuconazole, a new antifungal from the azole class, with a broader pathogen spectrum, was introduced in Sweden. A model has therefore been developed to compare the cost-effectiveness of isavuconazole and voriconazole in the treatment of possible IA in adults in Sweden.MethodsThe cost-effectiveness of isavuconazole versus voriconazole was evaluated using a decision-tree model. Patients with possible IA e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 34 publications
4
34
0
Order By: Relevance
“…In terms of cost-effectiveness, the US model estimated that isavuconazole was dominant in terms of the incremental cost per death avoided and the incremental cost per responder. A Swedish model published in 2019 assessed the cost-effectiveness of isavuconazole vs voriconazole for the treatment of patients who, at the point of treatment initiation, did not have a confirmed differential diagnosis between IA and mucormycosis, in terms of incremental cost per QALY based on data from the SECURE trial, and case-control analysis between the VITAL study and FungiScope registry 41 . The Swedish model results also favored the use of isavuconazole with 0.3 more QALYs per patient than voriconazole at an incremental cost of 52,191 Swedish krona (SEK), resulting in an ICER of 174,890 SEK per additional QALY gained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of cost-effectiveness, the US model estimated that isavuconazole was dominant in terms of the incremental cost per death avoided and the incremental cost per responder. A Swedish model published in 2019 assessed the cost-effectiveness of isavuconazole vs voriconazole for the treatment of patients who, at the point of treatment initiation, did not have a confirmed differential diagnosis between IA and mucormycosis, in terms of incremental cost per QALY based on data from the SECURE trial, and case-control analysis between the VITAL study and FungiScope registry 41 . The Swedish model results also favored the use of isavuconazole with 0.3 more QALYs per patient than voriconazole at an incremental cost of 52,191 Swedish krona (SEK), resulting in an ICER of 174,890 SEK per additional QALY gained.…”
Section: Discussionmentioning
confidence: 99%
“…A US cost-effectiveness evaluation found isavuconazole to be a cost-effective treatment option relative to voriconazole in hospitalized patients with IA 40 . Another cost-effectiveness analysis took a Swedish healthcare payer perspective and found treatment of possible IA (at the point of treatment initiation, a differential diagnosis between IA and mucormycosis had not been achieved) with isavuconazole to be cost-effective compared with voriconazole 41 . Furthermore, cost-minimization models in Italy 42 , Germany 43 , and the UK 44 estimated that isavuconazole is cost-saving relative to liposomal amphotericin B (L-AMB) followed by posaconazole in the treatment of mucormycosis and of invasive mold disease in general 45 .…”
Section: Introductionmentioning
confidence: 99%
“…Several economic analyses of isavuconazole vs voriconazole for the treatment of IA have been conducted in different countries: in hospitalised patients with IA in the United States 17 and in patients with possible IA in Sweden 18 and the UK 19 . Cost‐minimisation models of isavuconazole vs L‐AMB followed by posaconazole for the treatment of IM have been also performed in Italy, 20 Germany 21 and the UK 22 .…”
Section: Introductionmentioning
confidence: 99%
“…All studies found that isavuconazole was cost-saving when compared to voriconazole. These cost savings included the cost of the drug, the cost of adverse events, and hospital readmissions [ 34 , 35 , 36 ].…”
Section: Clinical Efficacymentioning
confidence: 99%